Coping strategies adopted by students and professors in the COVID-19 pandemic context: a cross-sectional study - Wottrich, Shana Hastenpflug; Mocellin, Lucas Pitrez; Ferrão, Camila Simonetti Pase; Bueno, Rovana Kinas; Vargas, Lais Alves (ABCS Health Sciences, 2023)
Introduction: In face of the COVID-19 crisis, classroom activities at universities were interrupted in Brazil, following the guidelines of health agencies to minimize coronavirus contamination levels, with implications for students’ and professors’ mental health. Objective: To identify the coping strategies used by students and professors of a Brazilian university during the COVID-19 pandemic, as well as the associated sociodemographic and institutional/academic variables. Methods: A cross-sectional survey was carried out using an online questionnaire with questions on socioeconomic aspects and applying the Ways of Coping Scale. Results: 671 students and 231 professors from a public university in the south of Brazil enrolled in the study. Students and professors used more problem-focused coping strategies followed by searching for social support. Regarding the professors, the variables frequency of leaving home and gender were positively associated with the problem and emotion-focused strategies and religion/fanciful thought strategies, respectively. Regarding the students, women used predominantly emotion-focused and religious/fanciful thought strategies. Students aged 27 or more used more problem-focused and 18-20 and 21-26 years old used predominantly emotion-focused strategies. Living with family and leaving home for 8 days or more were associated with the religious/fanciful thought strategy. Conclusion: Attention should be given to gender, age, and frequency of leaving home, when planning mental health actions to foster the use of a wider range of coping strategies adopted by university students and professors throughout moments of developmental crisis, such as the ones that emerged across pandemics.